Effects of human activities and low-frequency climate variability on East Asian temperature changes at century scale - Chun-Hui Lu; Ying Sun (Advances in Climate Change Research)
East Asia is one of the most densely populated regions in the world. Understanding the human causes of temperature changes, especially at the century scale, is important for climate change adaptation and mitigation. However, the attribution study of extreme temperature remains inadequate because of limited observational data from early historical periods. Here, we utilise multiple observational data and simulations from the Coupled Model Intercomparison Project Phase 6 to investigate the influence of external forcing and low-frequency climate variability from sea surface temperature on the changes in daily maximum (Tmax), minimum temperature (Tmin) and their difference (diurnal temperature range, DTR) during the period of 1901–2020. We find that the warming trends in East Asia differ across seasons, with the warming magnitudes in spring and winter greater than those in the other two seasons. Detection and attribution based on an optimal fingerprinting method show that anthropogenic forcing mainly explains the observed changes in Tmax and Tmin during 1901–2020. Greenhouse gas forcing contributes approximately 1.1 °C (90% confidence intervals (CI): 0.78–1.3 °C) and 1.4 °C (90% CI: 1.19–1.58 °C) of annual Tmax and Tmin changes, while the anthropogenic aerosol forcing offsets 0.47 °C (90% CI: 0.15–0.92 °C) and 0.4 °C (90% CI: 0.07–0.77 °C) of the warming. For the DTR, the anthropogenic signal could not be detected due to the small signal-to-noise ratio. Meanwhile, the effects of the low-frequency climate variability coming from the Atlantic Multidecadal Oscillation are small and mainly attributed to the warming of the Atlantic Ocean induced by global change. This attribution information strengthens the scientific basis and helps decision-makers develop effective strategies and plans.